Fabrication of Redox‐ and pH‐Sensitive Self‐Assembled Nano‐Micelles with Pegylated β‐Cyclodextrin for Codelivery of Doxorubicin and Cyclopalladated Ferrocene. Issue 8 (18th February 2022) - Lu, Xiangyu; Du, Guoyuan; Zhang, Zhonghui; Gong, Guidong; Cai, Wentao; Wu, Liji; Zhao, Gang
Abstract: We report a dual‐responsive, self‐assembled nano micelle for co‐delivery of doxorubicin (DOX) and a previously reported cyclopalladated anti‐cancer agent (CP). In this micelle system, doxorubicin and CP were electrostatically complexed to form a hydrophobic core while a conjugation of polyethylene glycol and β ‐cyclodextrin (CD) was designed to construct the hydrophilic out‐layer and stabilize the micelle. The interaction between pegylated CD and DOX‐CP composite was achieved via inclusion of ferrocene moiety by CD, which could be broken by stimulating ROS that is over‐expressed in many cancer cell lines. Moreover, the DOX‐CP adduct can be destabilized under an acidic environment that exists in most solid tumors, which can further disassemble the micelle and release the two drugs. The fabricated micelle was characterized by TEM, DLS and its stimulus‐responsive characteristic were confirmed by drug‐release profile. The in vitro cellular cytotoxicity was also evaluated, which showed improved anti‐cancer effect of drug‐loaded micelle compared to free drugs. Abstract : We fabricated a dual‐responsive, self‐assembled nanomicelle for co‐delivery of doxorubicin and a previously reported cyclopalladated anti‐cancer agent (CP). The in vitro cellular cytotoxicity was also evaluated, which showed an improved anti‐cancer effect of the drug‐loaded micelle compared to free drugs. We believe the nano‐drug delivery system reported in this work could be a potential alternative in clinical applications.